2019 International Conference on Smart Grid Synchronized Measurements and Analytics (SGSMA) 2019
DOI: 10.1109/sgsma.2019.8784556
|View full text |Cite
|
Sign up to set email alerts
|

Mode Shape Estimation using Complex Principal Component Analysis and k-Means Clustering

Abstract: We propose an empirical method for identifying low damped modes and corresponding mode shapes using frequency measurements from a Wide Area Monitoring System. The method consists of two main steps: Firstly, Complex Principal Component Analysis is used in combination with the Hilbert Transform and Empirical Mode Decomposition to provide estimates of modes and mode shapes. The estimates are stored as multidimensional points. Secondly, the points are grouped using a clustering algorithm, and new averaged estimate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The continually decreasing angle before t = 310 s indicates that the frequency of oscillations is slightly lower than the mean frequency used as input to the method, while the opposite is true for the period after t = 310 s. Observing that the trajectories of both the amplitude and angle make distinct turns at the same time could indicate that some remedial action was applied that changed the operating point. The same observation is also made in [8].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The continually decreasing angle before t = 310 s indicates that the frequency of oscillations is slightly lower than the mean frequency used as input to the method, while the opposite is true for the period after t = 310 s. Observing that the trajectories of both the amplitude and angle make distinct turns at the same time could indicate that some remedial action was applied that changed the operating point. The same observation is also made in [8].…”
Section: Discussionsupporting
confidence: 78%
“…The work presented is a continuation of previous research on power oscillation monitoring. In [8], [9], it is shown that the frequency and observability mode shape of oscillatory modes can be estimated within seconds after standing oscillations appear in measurements. This motivates the development of monitoring and control applications that make use of this information.…”
Section: Introductionmentioning
confidence: 99%
“…The description of the technique is presented below based on what is presented in the researches [1,19,20]. Each row of the data matrix represents the temporal evolution of the monitored measurements or data processed by WAMS system at time t. That is, the variables obtain operation level, and it is appropriately structured so operation matrix name X (instantaneous) of m x n dimensions, as shown in section 2.3.3.…”
Section: Power System Stabilizersmentioning
confidence: 99%
“…The basic structure of the method (CPCA dynamics decomposition combined with clustering for averaging) has been described previously in [11], where it is applied to analysis of large disturbances/ringdowns. Continuing this work, we propose further development of the method by introducing the DBSCAN clustering algorithm, in addition to further testing on a medium size grid and on ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Section II gives a description of the method, based on the more thorough description in [11], however with some modifications. Section III describes results from applying the method to simulated and recorded PMU data, followed by discussions and conclusions in Sections IV and V.…”
Section: Introductionmentioning
confidence: 99%